Reversible Redox System of 2‐Oxypyritriphyrin(1.2.1) Accompanying Interconversion between 3‐Pyridone and 3‐Hydroxypyridine Units. Issue 9 (31st March 2021) - Chong, Su‐Gi; Yoneda, Tomoki; Ide, Yuki; Neya, Saburo
Abstract: To develop a system in which a π‐conjugation circuit switched by a redox reaction between 3‐pyridone and 3‐hydroxypyridine, a ring‐contracted analog of oxypyriporphyrin, 2‐oxypyritriphyrin(1.2.1) was synthesized for the first time. 2‐Oxypyritriphyrin(1.2.1) contains a 14π aromatic conjugation circuit with the keto‐form of the 3‐oxypyridine ring. When 2‐oxypyritriphyrin was treated with NaBH4, not only the 3‐oxypyridine group, but also the meso ‐carbons were also reduced to give a colorless porphyrinogen analog. The reduced compound could be oxidized again to provide 2‐oxypyritripyhrin in a reversible manner. Abstract : To develop a π‐conjugation circuit switched by a redox reaction between 3‐pyridone and 3‐hydroxypyridine, a ring‐contracted analogue of oxypyriporphyrin, 2‐oxypyritriphyrin(1.2.1) was prepared. When 2‐oxypyritriphyrin was treated with NaBH4, not only the 3‐oxypyridine unit, but also the meso ‐carbon was also reduced. The reduced analog could be oxidized again to afford 2‐oxypyritriphyrin in a reversible manner.